(untitled) (Dhaka University Law Journal, 2025)
The human-rights based approach (HRBA) aims to empower the rights-holders in a fashion that they become able to ask for their lawful demands and rights under the provisions of the law and policies concerned. It depends on five core principles commonly known as PANEL (participation, accountability, non-discrimination and equality, empowerment and legality). It also investigates the capability and functions of the duty holders to find out whether they can perform their obligations in line with those recognised principles. In this given context, the article analyses the Bangladeshi legal aid system and demonstrates that it has progressed substantially in terms of the adoption of relevant laws and policies. The government has also taken various positive initiatives to implement the programme at the national level. However, the system is suffering from various drawbacks that not only deny the principles of the HRBA but also hinder the poor’s ability to obtain justice. The author, therefore, recommends some measures that might be useful in improving the system and bringing it into conformity with the principles of the HRBA. Dhaka University Law Journal, 2025, 36 (1), 27-37